Do players in Spanish professional soccer leagues maintain match running performance until the end of the match? A 5-minute interval analysis by match participation - García-Calvo, Tomás; Lobo-Triviño, David; Ponce-Bordón, José; Sanabria-Pino, Borja; López del Campo, Roberto; Resta, Ricardo; Chmura, Paweł (Biology of Sport, 2025)
The present study aimed to analyse the match running performance differences across 5‑minute time intervals considering the players’ participation in matches. A total of 381,194 individual match observations from professional soccer players competing in the First ( n = 171,957) and Second ( n = 209,237) Spanish soccer leagues over the 2022/23 season were collected. Soccer players were classified according to their participation in matches. Total distance (TD), very high-speed running (VHSR, 21–24 km × h −1 ), and sprinting speed running distance (Sprint, > 24 km × h −1 ) were analysed using a computerized tracking system (TRACAB, Chyronhego, New York, NY). Match data were divided into pre-defined 5-minute intervals. Linear mixed models were performed to analyse match running performance over the 5-minute intervals while controlling the influence of match participation. The main results showed a decrease in match running performance as the match time progressed, from the 55th–60th minute onward ( p < .001), although match participation also had a significant influence. Specifically, substitute players covered significantly greater VHSR ( p < .001) and Sprint distances ( p < .001) than the rest of the players during their time of participation. These findings provide knowledge about the evolution of match running performance over match time. Finally, analysis of 5-minute intervals may help coaches understand the periods of matches where player substitutions are most effective.